2015
DOI: 10.1016/j.bbamcr.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of actin filaments in fusopod formation and osteoclastogenesis

Abstract: Cell fusion process is a critical, rate-limiting step in osteoclastogenesis but the mechanisms that regulate fusopod formation are not defined. We characterized fusopod generation in cultured pre-osteoclasts derived from cells stably transfected with a plasmid that expressed a short, actin filament binding peptide (Lifeact) fused to mEGFP that enables localization of actin filaments in living cells. Fusion was initiated at fusopods, which are cell extensions of width >2 μm and that are immunostained for myosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 57 publications
1
33
0
1
Order By: Relevance
“…Less frequently, filopodium-like protrusions that formed after a transient expansion of podosome-like protrusions were observed. Wang et al have also observed finger-like extensions (~ 2.5 µm) in RAW264.7 cultures, which they termed fusopods (Wang et al, 2015). In that investigation, fusopods were the predominant structures, although some cells reportedly fused at contacts between broad surfaces.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Less frequently, filopodium-like protrusions that formed after a transient expansion of podosome-like protrusions were observed. Wang et al have also observed finger-like extensions (~ 2.5 µm) in RAW264.7 cultures, which they termed fusopods (Wang et al, 2015). In that investigation, fusopods were the predominant structures, although some cells reportedly fused at contacts between broad surfaces.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, a number of studies have reported the involvement of membrane extensions during osteoclastogenesis (Oikawa et al, 2012;Soe et al, 2015;Wang et al, 2015). Using RAW264.7 macrophages differentiated into osteoclasts by M-CSF and RANKL, Oikawa et al demonstrated that cell-cell fusion was mediated by short membrane protrusions that emerged from the sealing belt, a structure formed in large multinucleated osteoclasts from a ring of "circumferential" podosomes (Oikawa et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Podosomes are organized in clusters at the beginning of differentiation, followed by evolvement into dynamic rings and final stabilization at the cell edge to form a podosome belt [Song et al, ; Ti et al, ]. The cell periphery of immature osteoclasts shows dendritic filopodial extensions, while mature osteoclasts exhibit smooth plasma membranes [Wang et al, ]. Mature osteoclasts can form a resorptive microenvironment consisting of a refuled border and an actin ring on the bone‐cell interface.…”
Section: Discussionmentioning
confidence: 99%
“…These analyses are powerful, but are not able to elucidate on the details of individual fusion events leading to this outcome. However, recently analyses of OC fusion in real‐time have been used to identify novel details with regard to the individual fusion partners, their molecular‐ and fusion‐characteristics (Takito and Nakamura, 2012; Takito et al, 2012; Levaot et al, 2015; Soe et al, 2015; Wang et al, 2015; Fiorino and Harrison, 2016). We have recently published a study (Soe et al, 2015), in which we analyzed a large quantity of time‐lapse recordings made over a period of 4 days.…”
mentioning
confidence: 99%